The ranking analysis of the petroleum and related products’ companies - ÇİLİNGİRTÜRK, AHMET METE; KOÇAK, HABİP; KİSTİK, VİLDAN (My University, 2017)
In competitive markets, companies search their positions according to their competitors with internal resources or make use of the services of market research firms. Various credit and rating agencies or co-ordination for sectors with some social and political remediation also examine and rank the companies in these sectors. These companies are listed on the Stock Exchange Istanbul. Petroleum and derivatives industries, which are important sources of energy for industrial and Turkey, have been reconsidered in the Fortune 500 ranking by MOORA and COPRAS optimization methods and with statistical factor analysis with various efficiency and size indicating financial ratios. The results obtained are consistent within themselves and differ from the Fortune 500 rank order. The difference between quality and quantity can lead companies to wrong strategies in this sort of ranking. The study might be important to bring out efficiency and productivity in the sense of planning possible strategic changes.
Keywords: Sosyal ve Beşeri Bilimler; Ekonometri; Yöneylem; Social Sciences and Humanities; Econometrics; Operational Research; Sosyal Bilimler (SOC); Ekonomi ve İş; OPERASYON ARAŞTIRMA VE YÖNETİM BİLİMİ; EKONOMİ; Social Sciences (SOC); ECONOMICS & BUSINESS; OPERATIONS RESEARCH & MANAGEMENT SCIENCE; ECONOMICS; Ekonomi ve Ekonometri; Ekonomi, Ekonometri ve Finans (çeşitli); Genel Ekonomi, Ekonometri ve Finans; Yönetim Bilimi ve Yöneylem Araştırması; Örgütsel Davranış ve İnsan Kaynakları Yönetimi; Sosyal Bilimler ve Beşeri Bilimler; Economics and Econometrics; Economics, Econometrics and Finance (miscellaneous); General Economics, Econometrics and Finance; Management Science and Operations Research; Organizational Behavior and Human Resource Management; Social Sciences & Humanities